The Psychometric Properties of the Norwegian version of Strengths and Difficulties Questionnaire, selvrapport (SDQ-S) - Kornør, Hege; Heyerdahl, Sonja (PsykTestBarn, 2013)
Description: The Strengths and Difficulties Questionnaire was originally published in English by Robert Goodman in 1997. The Norwegian versions were published in 1999, based on a translation and back-translation by Einar Heiervang and colleagues. Robert Goodman holds the copyright. The SDQ-S contains 25 items organized in five subscales. It is a self-report form to assess mental health, peer relations and prosocial behavior in youth aged 11-16 years, and takes a few minutes to complete. Clinicians, researchers and teachers can administrate and interpret the SDQ-S. Literature search: Our systematic searches for psychometric evidence for the Norwegian SDQ-S version identified 252 references, of which 27 publications from 14 studies were included. Twenty publications were reports from large population-based studies with a total of 39571 participants in Bergen, Oslo, Akershus, Nord-Trøndelag and northern Norway. Psychometrics: The large population-based studies contributed with regional norm data distributions by age and gender. Researchers assessed the SDQ-S factor structure in three studies, and one study reported diagnostic accuracy data. Group comparisons between subgroups and controls also addressed the instrument’s validity. We identified measures of internal consistency (Cronbach’s alpha) from six studies. Conclusion: The SDQ-S is a short form, but the evidence for its ability to detect youth with mental health problems is insufficient in order to recommend it as a screening instrument. The SDQ-S has regional norms that vary somewhat between the regions, but there is a lack of national data. Expected groups differences and confirmatory factor analyses support the construct validity of the instrument. The subscale Emotional symptoms has adequate internal consistency, but the remaining subscales’ internal consistencies are below an adequate level.